A Prior History of Substance Abuse in Veterans Undergoing Bariatric Surgery - Maureen Tedesco; William Q. Hua; Jessica A. Lohnberg; Nina Bellatorre; Dan Eisenberg (Hindawi Limited, 2013)
Background. The rates of obesity and substance abuse are high among US veterans. Objective. To examine weight loss and substance abuse rates following bariatric surgery in veterans with a history of substance abuse (SA). Methods. A prospective database of consecutive bariatric operations was reviewed. Data for SA patients were compared to patients without a substance abuse history (NA). Behavioral medicine staff followed patients throughout the pre- and postoperative courses. Results. Of 205 bariatric surgery patients, there were 74 (36.1%) SA patients. The mean preoperative body mass index (BMI) was 46.2 ± 8.1 kg/m2, and percent excess weight loss at 12 months was 71.8%, 58.0%, and 33.5% for Roux-en-Y gastric bypass, laparoscopic sleeve gastrectomy, and laparoscopic gastric banding, respectively, not significantly different than the NA group (, 0.75, 0.96). Postoperative substance abuse in SA and NA patients was 8.1% and 1.5%, respectively (). Conclusion. A prior history of substance abuse is common in veterans undergoing bariatric surgery; weight loss results are comparable to the general veteran bariatric cohort. Rates of substance abuse are low postoperatively, but higher in patients without a prior history of substance abuse. Close multidisciplinary followup throughout the postoperative course is likely to be integral to the patient's success.